Reported roles of care partners in a specialized weaning centre—perspectives of patients, care partners, and health care providers - Istanboulian, L.; Gilding, A.; Hamilton, L.; Master, T.; Bingler, S.; Hill, M.; Isani, S.; Kazi, S.; Coppinger, S.; Smith, K. (Frontiers in Health Services, 2024)
BackgroundCare partners are individuals chosen by a person with an illness to support their care during hospitalization. Patients with persistent critical illness have longer than average critical care admission and often other conditions including dysphagia, communication vulnerability, severe physical deconditioning, the need for an artificial airway, and difficulty weaning from invasive mechanical ventilation. Family presence has been identified as important for patients experiencing persistent critical illness in specialized weaning centers. Despite this, the role of care partners in clinical settings for patients with persistent critical illness has not been fully characterized, particularly from the perspectives of patients, care partners, and health care providers. The aim of this study was to gain insights into the roles of care partners during persistent critical illness from the perspectives of patients, care partners, and health care providers.MethodsWe used qualitative descriptive methodology including semi-structured interviews and content analysis. Interviews were audio recorded and transcribed verbatim. Included participants (n = 30) were patient survivors (n = 7), care partners of patient survivors (n = 9), and professionally diverse health care providers (n = 14) of adult patients with persistent critical illness from two specialized units in one community academic hospital in Toronto, Canada.ResultsParticipants across all groups described care partner roles that included physical, mental health, cognitive, social, and spiritual support of the patient, including the perceived role of safeguarding the multiple dimensions of care for the patient who is experiencing persistent critical care in specialized care settings.DiscussionThe results of this study are being used to co-design, implement, and evaluate a sustainable care partner program that is acceptable, appropriate, and feasible to implement in clinical settings where the care of patients with persistent critical illness occurs.Reporting methodConsolidated criteria for reporting qualitative studies (COREQ).